Dietary Acid Load Modulation of Asthma-Related miRNAs in the Exhaled Breath Condensate of Children - Mendes, FC (2022)
Individual nutrients and bioactive compounds have been implicated in the expression of microRNAs (miRNAs), which are related to inflammation and asthma. However, evidence about the impact of diet is scarce. Therefore, we aimed to assess the association between dietary acid load and asthma-related miRNA in the exhaled breath condensate (EBC) of school-aged children. This cross-sectional analysis included 150 participants aged 7 to 12 years (52% girls) from a nested case-control study, which randomly selected 186 children attending 71 classrooms from 20 public schools located in city of Porto, Portugal. Dietary data were collected by one 24 h-recall questionnaire. Dietary acid load was assessed using the potential renal acid load (PRAL) and net endogenous acid production (NEAP) scores. Based on previous studies, eleven asthma-related miRNAs were chosen and analyzed in EBC by reverse transcription-quantitative real-time PCR. PRAL, NEAP and miRNAs were categorized as high or low according to the median. Logistic regression models were performed to assess the association between dietary acid load scores and miRNAs. Children in high dietary acid load groups (PRAL >= 14.43 and NEAP >= 55.79 mEq/day) have significantly increased odds of having high miR-133a-3p levels. In conclusion, higher dietary acid loads possibly modulate asthma-related miRNAs of school-aged children.